2007
DOI: 10.1152/ajpheart.00037.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in cardiac dysfunction of PPARα−/−mice

Abstract: This study was designed to determine the effects of PPARalpha lack on cardiac mechanical performance and to identify potential intracellular mechanisms linking PPARalpha pathway deficiency to cardiac contractile dysfunction. Echocardiography, ex vivo papillary muscle assays, and in vitro motility assays were used to assess global, intrinsic ventricular muscle performance and myosin mechanical properties, respectively, in PPARalpha(-/-) and age-matched wild-type mice. Three-nitrotyrosine formation and 4-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…This explanation would be compatible with the higher coronary flow of PPAR␣ null mouse hearts at the higher preload. Incidentally, a recent study by Guellich et al (15) demonstrated oxidative damage to contractile proteins, specifically tyrosine nitration of myosin, in these hearts, suggesting an increased production of free radicals and nitric oxide. This may also offer an explanation for the change in activity of NADP ϩ -isocitrate dehydrogenase, an enzyme that is affected by oxidative stress-related molecules.…”
Section: Discussionmentioning
confidence: 91%
“…This explanation would be compatible with the higher coronary flow of PPAR␣ null mouse hearts at the higher preload. Incidentally, a recent study by Guellich et al (15) demonstrated oxidative damage to contractile proteins, specifically tyrosine nitration of myosin, in these hearts, suggesting an increased production of free radicals and nitric oxide. This may also offer an explanation for the change in activity of NADP ϩ -isocitrate dehydrogenase, an enzyme that is affected by oxidative stress-related molecules.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies found that cardiac PPARa deficiency led to significant decrease of LV SOD2 expression (8). Further studies demonstrated that the absence of PPARa results in a more pronounced hypertrophic growth response and signs of functional deterioration (28).…”
Section: Discussionmentioning
confidence: 94%
“…Each PPAR typic changes. In a study reporting cardiac contractile dysfunction in PPARα null mice, a mechanism of oxidative damage in sarcomere proteins and lipid peroxidation was proposed based on the observation that a significant decrease of SOD2 protein and the corresponding activity with no change of other antioxidant enzymes such as Cu/ZnSOD (SOD1), catalase, and glutathione peroxidase (GPx) was reported [46] . It is not clear if the repression of SOD2 protein level and activity also occurred at the transcript level.…”
Section: Subtype Specific Role Of Ppars On the Regulation Of Redox Pamentioning
confidence: 99%